Examining the Role of Resilience and Hope in Grit in Multiple Sclerosis - Lee, Beatrice; Rumrill, Phillip; Tansey, Timothy N. (Frontiers in Neurology, 2022)
The purpose of this study was to examine the effects of resilience and hope on grit when controlling for demographic covariates, depression, and anxiety in people with multiple sclerosis (MS). This was a cross-sectional study with a sample of 348 participants with MS. Descriptive statistics were performed to examine participants’ demographic characteristics. A three-step hierarchical regression analysis was conducted to evaluate the extent to which resilience and hope explain the unique variance in grit while controlling for demographic covariates, depression, and anxiety. Findings suggested that resilience and hope explained a significant amount of variance in grit when controlling for demographic covariates, depression, and anxiety. Furthermore, higher resilience and hope scores were associated with higher grit scores. Given that resilience, hope, and grit are modifiable, rehabilitation and mental health professionals (e.g., psychologists, psychiatrists, rehabilitation counselors) can integrate strength-based interventions into their practices to bolster resilience, hope, and grit in people with MS. Our paper also has implications for interdisciplinary research and clinical practice.